Extrinsic calibration of a camera-robot system under non-holonomic constraints - Araguás, Gastón (2011)
A novel approach for the extrinsic calibration of a camera-robot system, i.e. the estimation of the pose of the camera with respect to the robot coordinate system, is presented. The method is based on the relative pose of a planar pattern as seen by the camera, estimated along with a predefined set of simple robot motions. This set has been generated so as to exploit the kinematic constraints imposed by the robot architecture and the relative pose between the pattern and the camera coordinate system. The resulting calibration procedure is very simple, making it suitable to be used in a broad range of applications. Experimental evaluations on both synthetic and real data demonstrate the validity of the proposed method.